Evaluation of heavy metals in different brands of chocolates marketed in Kathmandu, Nepal, and their associated health risks - Maharjan, Jasana; Shakya, Pawan Raj (Journal of Nepal Chemical Society, 2024)
Chocolates are among the sweet food items consumed by all age groups particularly children in Nepal. However, this foodstuff may be contaminated with heavy metals from the raw ingredients, production, and packaging methods, which could bring serious health issues. Therefore, this study aimed to determine cadmium (Cd), nickel (Ni), and lead (Pb) by Flame Atomic Absorption Spectrophotometer (FAAS) in a total of thirty-seven different brands of milk-based, cocoa-based, and sugar-based chocolates available in local grocery shops of Kathmandu city, Nepal and to evaluate associated health risks in children and adults using USEPA deterministic approaches. The results revealed concentrations of Cd, Ni, and Pb in the range of 0.021 – 0.585, 1.90 – 7.24, and 0.57 – 4.29 mg/kg respectively in studied chocolates and an overall mean concentration of 0.199, 4.22, and 1.94 mg/kg respectively. The observed concentrations exceeded the maximum permissible limits set by FAO/WHO (2001). A higher concentration of all studied metals was found in cocoa-based chocolate compared to milk-based and sugar-based chocolates. The positive and significant correlations (p < 0.05) among Cd, Ni, and Pb in studied chocolates indicate the possibility of contamination from common sources. Similarly, the estimated ADDing values were higher for all metals in cocoa-based chocolate for both children and adults. However, children were more prone to metals exposure than adults since their dietary intake was higher than adults. Cocoa-based chocolate in this study posed a non-carcinogenic risk to both children and adults since their hazard index (HI) values exceeded the acceptable limit (>1.0). In addition, Cd and Ni posed carcinogenic risks to both receptor groups through the consumption of all three categories of chocolate. Therefore, this study suggested the use of less contaminated raw materials in chocolates as well as regular monitoring of the production chain as an attempt to ensure the quality and safety of the food products.